Convergence and divergence of molecular mechanisms in Hebbian and homeostatic plasticity - Feighan, Kira M.; Thakare, Harshit K.; Glasgow, Stephen D.; Kennedy, Timothy E. (Frontiers in Synaptic Neuroscience, 2026)
The umbrella of synaptic plasticity includes associative, activity-dependent alterations in synaptic strength that are thought to underlie learning and memory, and negative feedback that stabilizes network activity, termed Hebbian and homeostatic plasticity, respectively. These forms of plasticity respond to activity oppositely, and on different spatial and temporal scales. However, despite these fundamental differences, many similar molecular mechanisms are engaged by each form of plasticity to alter synaptic strength. Here, we review molecular mechanisms involved in homeostatic plasticity and compare their involvement in Hebbian plasticity. We focus on synaptic scaling, long-term potentiation, and long-term depression, which are mediated by regulation of post-synaptic amino-3-hydroxyl-5-methyl-4-isoxazole-propionate-type glutamate receptor (AMPARs) accumulation. Addressing synaptic scaffolding, intracellular signaling, cell-adhesion, and secreted factors, we identify mechanisms that appear to be convergent, differentially engaged, and divergent that uniquely regulate homeostatic scaling. These comparisons identify clear gaps to be addressed by future studies that aim to parse the contributions of Hebbian and homeostatic plasticity to regulate AMPAR function.